2017
DOI: 10.3390/ijerph14101284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Utero Exposure to Di-n-Butyl Phthalate on Testicular Development in Rat

Abstract: Humans are inevitably exposed to ubiquitous phthalate esters (PAEs). In utero exposure to di-n-butyl phthalate (DBP) induces abnormal development of the testis and reproductive tract in male offspring, which correspond closely with the human condition of testicular dysgenesis syndrome (TDS)-like syndrome. However, the underlying mechanisms have not been elucidated in detail. In this study, pregnant rats were orally exposed to either corn oil (controls) or DBP at three different doses by gavage during Gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 50 publications
2
17
0
3
Order By: Relevance
“…As an environmental endocrine disruptor, DBP has certain male reproductive toxicity, can cause male rodents testicular atrophy, weight loss, decreased testicular activity of the enzyme, seminiferous tubules atrophy, spermatogenic cell loss, genital malformations, etc. [17]. In this vivo study of testicular pathology showed that DBP lead to testicular tissue structure damage, manifested as spermatogenic tubule disorders, Sertoli cell vacuolization, germ cell shedding, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…As an environmental endocrine disruptor, DBP has certain male reproductive toxicity, can cause male rodents testicular atrophy, weight loss, decreased testicular activity of the enzyme, seminiferous tubules atrophy, spermatogenic cell loss, genital malformations, etc. [17]. In this vivo study of testicular pathology showed that DBP lead to testicular tissue structure damage, manifested as spermatogenic tubule disorders, Sertoli cell vacuolization, germ cell shedding, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, male reproductive problems, such as spermatogenesis disorders, infertility, and premature abortion, have become more prevalent worldwide [1]. It is worth noting that infertility affects an estimated 15% of couples globally, and males were believed to contribute to 50% of cases overall [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some formulations of 5-ASA drugs include dibutyl phthalate (DBP) in the enteric coating, which had been associated with skeletal formations and urogenital defects in male offspring of exposed female rates. 35,36 In a report of six cases, urinary concentrations of phthalate metabolites in patients treated with DBP-containing 5-ASA formulations were 50 times higher than those not treated with these formulations. 37 The effects seen in animal models have not been seen in humans.…”
Section: Pharmacologic Therapiesmentioning
confidence: 98%